Transparency and Liquidity: A Comparison of Auction and Dealer Markets with Informed Trading - PAGANO, MARCO; RÖELL, AILSA (Journal of Finance, 1996)
ABSTRACT Trading systems differ in their degree of transparency, here defined as the extent to which market makers can observe the size and direction of the current order flow. We investigate whether greater transparency enhances market liquidity by reducing the opportunities for taking advantage of uninformed participants. We compare the price formation process in several stylized trading systems with different degrees of transparency: various types of auction markets and a stylized dealer market. We find that greater transparency generates lower trading costs for uninformed traders on average, although not necessarily for every size of trade.